The gender pay gap in university student employment - Paul David Bolls; Lukas Mergele; Larissa Zierow (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Gender pay gaps are commonly studied in populations with already completed educational careers. We focus on an earlier stage by investigating the gender pay gap among university students working alongside their studies. With data from five cohorts of a large-scale student survey from Germany, we use regression and wage decomposition techniques to describe gender pay gaps and potential explanations. We find that female students earn about 6% less on average than male students, which reduces to 4.1% when accounting for a rich set of explanatory variables. The largest explanatory factor is the type of jobs male and female students pursue.
Keywords: I22; I23; J16; J31; 330; Gender pay gap; university student employment; job types